Questions of religious truth. - Smith, Wilfred Cantwell, 1916-2000. (London, Gollancz, 1967)
Questions asked and answered by a Harvard professor. For contents, see Author Catalog.
The "Death of God"? -- Is the Qur'an the word of God? -- Can religions be true or false? -- Christian--noun, or adjective?
Includes bibliographical references.
Keywords: Religion; Truth